Development of Reading Enrichment Books Integrating Humanistic Values and 21st Century Skills for Pre-Service Teachers - Nurhabibah, Prabawati; Subyantoro, Subyantoro; Pristiwati, Rahayu; Haryadi, Haryadi; Wilson, Joseph (Pandawan, 2025)
This study aims to develop and measure the effectiveness of early reading enrichment books that integrate humanist values, 21st-century skills, and entrepreneurial dimensions for primary school students. Based on needs analysis, the enrichment books are designed not only to improve reading skills but also to support the development of critical thinking, collaboration, empathy, and creativity. The results from the pretest and posttest show a significant improvement, with an average pretest score of 45.50 and a posttest score of 75.10, showing a difference of 29.60 points. Analysis using the paired t-test produced a t-value of -10.99 with a significance value (p-value) of 0.000, indicating that the difference in learning outcomes is statistically significant. This research is also supported by several recent literatures that highlight the importance of integrating 21st-century skills, entrepreneurial dimensions, and humanist values in learning. Although the results of this study are positive, there are some limitations, such as the limited sample size and focus solely on reading skills. Further research is recommended to expand the range of skills measured, as well as to link the use of technology, local culture, and examine the long-term effectiveness of these enrichment books.